Collateral benefits from a school‐readiness intervention on breastfeeding: A cross‐domain impact evaluation. Issue 1 (11th October 2022) - Miller, Elizabeth B.; Whipps, Mackenzie D. M.; Bogen, Debra L.; Morris, Pamela A.; Mendelsohn, Alan L.; Shaw, Daniel S.; Gross, Rachel S.
Abstract: This study evaluated the collateral, or unanticipated, impacts of Smart Beginnings (SB), a two‐site, tiered intervention designed to promote responsive parenting and school readiness, on breastfeeding intensity in a low‐income sample. Impact analyses for the SB intervention were conducted using an intent‐to‐treat design leveraging a two‐arm random assignment structure. Mothers assigned to the SB intervention group were more than three times more likely to give breastmilk as the only milk source at infant age 6 months than mothers assigned to the control group at one site, an effect not evident at the other study site. As development and growth are the two most salient domains of child health, understanding how interventions impact subsequent parenting practices across both domains is critical to address long‐term economic and racial/ethnic disparities. Implications of the findings are discussed for improving the efficacy of interventions based on paediatric primary care. Abstract : We found that the Smart Beginnings (SB) intervention increased the rates of providing breast milk as the only milk source in the study site with low initial rates of breastfeeding. Our study contributes to the small, but growing, literature on the potential health benefits of early learning interventions and extends these findings to breastfeeding, a key indicator of infant nutrition. It further adds to the study of collateral programme benefits in adapting interventions across contexts and maximising positive outcomes Key messages: We found that the Smart Beginnings (SB) intervention increased the rates of providing breast milk as the only milk source in the study site with low initial rates of breastfeeding. Our study contributes to the small, but growing, literature on the potential health benefits of early learning interventions and extends these findings to breastfeeding, a key indicator of infant nutrition. It further adds to the study of collateral programme benefits in adapting interventions across contexts and maximizing positive outcomes. The policy implications of our study indicate how the medical home model of care can leverage limited resources for intervention delivery. Collateral benefits to additional outcomes, combined with programmatic knowledge, suggest that school readiness parenting programmes like SB may have impacts beyond child development. This study further adds to a growing literature that parenting interventions based in paediatric primary care may lead to synergistic effects across domains using a single intervention model. These findings illustrate that primary care clinics that host parenting interventions may leverage resources with cross‐domain spillover effects in mind, as collateral benefits can continue to provide helpful information about integrated models more broadly.